Penerapan Video Editing sebagai Inovasi Promosi Kesehatan di Puskesmas Kedungsolo: Solusi Kreatif untuk Edukasi Masyarakat - Andriyani, Fitriya; Dian Kartika Sari; Lintang Anis Bena Kinanti; Malinda Capri Nurul Satya (Jurnal Pengabdian Masyarakat dan Lingkungan (JPML), 2025)
Health promotion is an important effort to increase public awareness about healthy living behaviour. In the digital era, innovation in the delivery of health information is the key to reaching audiences more effectively. This article discusses the implementation of video editing as an innovative tool to support health promotion at the Kedungsolo Community Health Centre. Through community service activities, the team provides training in creating and editing educational videos to staff. This training covers basic concepts of video editing, use of software, and strategies for delivering health messages that are interesting and easy to understand. The results of the activity show that staff are able to produce quality informative videos that are distributed via social media and other digital platforms. These videos have succeeded in increasing community participation in health centre health, such as immunizations, health checks and disease prevention. By implementing this technology, Kedungsolo Community Health Centre can optimize digital-based health promotion to reach more people at large.